Peran Gaya Kepemimpinan Transformasional dan Transaksional dalam Penerapan Strategi Bisnis Masa Pandemi Covid-19: Studi Kasus pada BUMD X - Jajang Ginanjar; Bambang Hermanto; Pratami Wulan Tresna (Bahtera Inovasi, 2022)
The Covid-19 pandemic has had a devastating impact on organizations. Organizational leaders must have competencies that are ready to face rapid environmental changes. Leaders are required to always be at the forefront and influence their subordinates to keep working optimally even in unexpected situations. As one of the affected organizations, Regional Owned Enterprises (ROE) X is trying to survive. This study discusses the leadership style of BUMD X leaders during the pandemic which involves the implementation of business strategies. The results show that the combination of transactional and transformational leadership styles is carried out by leaders in BUMD X, autocratic leadership styles have a bad effect, and transactional and transformational leadership styles can be applied to business strategies during the Covid-19 pandemic. Therefore, the results obtained in this study are expected to be input for academics and business leaders to be applied to various similar and dissimilar organizations.